THE POWER OF RELIGION IN IMPROVING LABOR'S WORK ETHIC: Kekuatan Agama Dalam Meningkatkan Etos Kerja Buruh - Shoni Rahmatullah Amrozi (Fenomena, 2019)
Religion is a system of belief or belief in the existence of something that is absolute outside of humans and is a system of human worship to that which is considered absolute, as well as a system of norms that regulates human relations with fellow human beings and human relations with other natural worlds that are appropriate and harmonious. with the system of faith and worship. This research discusses the manifestation of the work ethic of Muslim workers at PTPN X Jember bobbin industrial unit and the meaning of Muslim worker's work ethic at PTPN X Jember bobbin industrial unit. This study concludes that there are forms of religious manifestations toward Muslim workers. It can be supposed that these forms include: congregational prayers, annual istighosah, and commemoration of Islamic holidays as a form of workers' motivation in religion. In addition, the understanding of the religion of the workers in this study is how someone who works as a laborer understands the religion he adheres to. The understanding of religion discussed is about faith, worship, and muamalah.